VR platform enabling crowdsourcing of embodied HRI experiments – case study of online robot competition. (3rd June 2021) - Inamura, Tetsunari; Mizuchi, Yoshiaki; Yamada, Hiroki
Abstract : The COVID-19 pandemic has made it difficult to conduct research involving human-robot interactions (HRIs). As a result, many robot competitions have been canceled in the past year. To address this problem, we propose a cloud-based VR platform for the crowdsourcing of embodied cognition with multiple human users and a virtual robot. The feasibility of the platform is evaluated from the latency of the interactive events and the motions of avatars, based on the number of users logging in to the VR scene and the distance between the local and server environments. We also discuss the feasibility of our system when dealing with large-scale datasets in embodied HRI experiments. GRAPHICAL ABSTRACT: UF0001